EFFICACY OF ULTRASOUND ELASTOGRAPHY IN LIVER FIBROSIS ASSESSMENT - Zuhur Mardha Aldawsari, ⁠‏Hana Mohammed Alanazi, ⁠Shodaiyed Masoud Fahadal Qahtani, ⁠Abdullah Muslatdohimalboqami, Mohammed Hamoud Saud Alharbi, ⁠Mashal Mohammed Salem Alanazi, Abdullah Fahad Mousa Mulhiyah, Rahmah Saleh Dhayif Alqarni; Naif Yahya Faye Al Samah, Hassan Mohammed Abdullahal Abdali, ⁠Salem Abdulaalim Hamidan Alsolami, ⁠Hasan Yousof abdul lmannanmarghalani (Chelonian Research Foundation, 2022)
Liver fibrosis is a characteristic feature seen in the tissue samples of the majority of chronic liver illnesses. It has the potential to advance to cirrhosis and liver failure, and also increases the likelihood of developing hepatocellular carcinoma. Precise identification of liver fibrosis is essential for determining the prognosis, categorizing the risk, and making decisions about therapy. Liver biopsy, which is considered the gold standard for evaluating liver fibrosis, is an intrusive procedure that is expensive and not suitable for routine monitoring of therapy response. Elastography provides a noninvasive, unbiased, and measurable substitute for liver biopsy. This article examines the need for noninvasive evaluation of liver fibrosis and evaluates the relative benefits and drawbacks of ultrasound and magnetic resonance elastography methods in terms of their fundamental principles, data collection, data analysis, and diagnostic accuracy. The analysis takes into account the different clinical circumstances in which the techniques are used and the typical mistakes that are connected with each one. Furthermore, this article examines the existing obstacles and potential future advancements aimed at enhancing the precision of elastography methods in diagnosing medical conditions and their practical usefulness in clinical settings.